Development status and prospect of underground gas storage in China - Jianjun LI (You-qi chuyun, 2022)
As the natural gas consumption increases at 10% annual rate of growth in China, the importance of stable energy supply is becoming increasingly prominent. Thus, the underground gas storage becomes very critical to peak shaving, stable supply and strategic reserve of natural gas. Herein, the shortcomings of construction, operation and technology in the current development of gas storage were put forward by investigating the increment of gas demand in China and the regional distribution characteristics of gas storage at present. The scope of site selection and construction of gas storage was expected to be more extensive, and thereby to form the networked and coordinated gas storage group under the background of striving to build a unified national network of natural gas in China. In the future, underground gas storage will develop towards the direction of intensive, efficient, intelligent, technological and economic development. The research results can provide reference to promote the construction of gas storage in the next step.